Carbapenem-Resistant Enterobacter cloacae in Patients from the US Veterans Health Administration, 2006–2015 - Brigid M. Wilson; Nadim G. El Chakhtoura; Sachin Patel; Elie Saade; Curtis J. Donskey; Robert A. Bonomo; Federico Perez (Emerging Infectious Diseases, 2017)
We analyzed carbapenem-resistant Enterobacteriaceae (CRE) trends among patients from the US Veterans Health Administration (VHA). After the emergence of CRE in the eastern United States, resistance rates remained stable in Klebsiella pneumoniae but increased in Enterobacter cloacae complex, suggesting a "second epidemic". VHA offers a vantage point for monitoring nationwide CRE trends.